PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PBB DI KECAMATAN BEJI KOTA DEPOK - Dipa Teruna Awaluddin; Hasanudin Hasanudin; Dwi Bunga Nur Mego Suci (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2023)
This study intends to examine the impact of taxpayer compliance in paying PBB on taxpayer awareness, tax knowledge, and tax sanctions on taxpayer compliance in paying PBB in Beji District, Depok City. Quantitative techniques are used in this research method. Primary data from distributing questionnaires to taxpayers registered in Beji District, Depok City, is used in the data collection technique. The population of PBB taxpayers registered in Beji District, Depok City, is 59,323 PBB taxpayers, and 100 respondents are the research sample. SPSS program version 25 is used to process data. Validity test, reliability test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), t test, F test, multiple linear regression analysis, and the coefficient of determination (R2 test) are the data analysis techniques used. The results showed that: (1) taxpayer awareness does not affect taxpayer compliance in paying PBB in Beji District, Depok City, (2) tax knowledge has a significant positive effect on taxpayer compliance in paying PBB in Beji District, Depok City, (3) tax sanctions have a significant positive effect on taxpayer compliance in paying PBB in Beji District, Depok City. Key words: taxpayer awareness, tax knowledge, tax sanctions, and taxpayer compliance